Ternary transition-metal fluoride precursors for the fluorolytic sol–gel route: new insights into speciation and decomposition1. Issue 29 (7th August 2015) - Kohl, J.; Wiedemann, D.; Troyanov, S. I.; Palamidis, E.; Lerch, M.
<x xml:space="preserve">Abstract</x> After successive, incomplete fluorination, complexes containing the motifs [MFn](3−n)+ (M = V, Mn, Ni; n = 0–4) have been trapped with pyridine and identified using X-ray diffraction.